2013
DOI: 10.1055/s-0033-1333696
|View full text |Cite
|
Sign up to set email alerts
|

Release of ANP and Fat Oxidation in Overweight Persons during Aerobic Exercise in Water

Abstract: Exercise in water compared to land-based exercise (LE) results in a higher release of natriuretic peptides, which are involved in the regulation of exercise-induced adipose tissue lipolysis. The present study was performed to compare the release of atrial natriuretic peptide (ANP) and free fatty acids (FFA) during prolonged aerobic water-based exercise (WE) with the release after an identical LE. 14 untrained overweight subjects performed 2 steady state workload tests on the same ergometer in water and on land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Two-third of the aquatic cycling sessions (n = 22) were conducted in an upright body position. Nine studies [11, 2426, 30, 31, 3436] compared semi-recumbent cycling on land and in water. Four semi-recumbent bikes also had arm pedals [11, 24, 30, 36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-third of the aquatic cycling sessions (n = 22) were conducted in an upright body position. Nine studies [11, 2426, 30, 31, 3436] compared semi-recumbent cycling on land and in water. Four semi-recumbent bikes also had arm pedals [11, 24, 30, 36].…”
Section: Resultsmentioning
confidence: 99%
“…Other key outcomes were ventilation parameters [23, 31, 33], lipid mobilisation and oxidation [18, 34], sympathoadrenal response [18, 20, 34], lactate accumulation and removal [17, 18, 20, 39, 40]. and thermoregulatory responses [3537].…”
Section: Resultsmentioning
confidence: 99%
“…FFA is produced through the hydrolysis of triglycerides by hormone sensitive lipase (HSL) in adipocyte cells, but insulin inhibits the activity of HSL (Holm, 2003). ANP has a strong stimulatory effect on adipose tissue lipolysis and is released from the atrial wall by increased blood volume in the atria (venous return) during exercise in water than on land (Fenzl et al, 2013). However, because there were no significant differences among exercise modes in serum insulin, it is necessary to consider other reasons why the serum FFA after the aquatic exercise was elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Wiesner et al (Wiesner et al, 2010) has reported that atrial natriuretic peptide (ANP) in a water exercise condition was significantly increased compared with that during a land exercise condition under the same _ VO 2 . ANP has a strong stimulatory effect on adipose tissue lipolysis and is released from the atrial wall by increased blood volume in the atria (venous return) during exercise in water than on land (Fenzl et al, 2013). On the other hand, because catecholamine stimulates FFA production (Mora-Rodriguez & Coyle, 2000) as well as ANP, enhanced catecholamine on land exercise has the potential to elicit serum FFA production compared with water exercise.…”
Section: Discussionmentioning
confidence: 99%
“…[18] who recently reported an increase of ANP from 29.8 ± 3.4 pmol/l to 82.5 ± 8.3 pmol/l. Assuming an increase from 35 to 55 with a SD of 10, we would need eight patients in each group to achieve 90% power at the 1% significance level (two-sided test).…”
Section: Methodsmentioning
confidence: 99%